1978
DOI: 10.1128/aem.36.5.693-699.1978
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of glycerol nitrates

Abstract: The fate of glycerol trinitrate when exposed to microbial attack has been investigated. Contrary to some earlier reports, this compound was readily biodegraded by employing batch or continuous techniques under a variety of cultural conditions. Breakdown of glycerol trinitrate took place stepwise via the dinitrate and mononitrate isomers, with each succeeding step proceeding at a slower rate. After a residence time of 8 to 15 h, none of the glycerol nitrates could be detected in the effluent from a continuous-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 8 publications
2
36
1
Order By: Relevance
“…This finding is in agreement with previous work that reported a 3.1% decrease in NG concentration in shake-flask experiments in the absence of growth substrates. 21 To further investigate the issue of NG as a sole carbon source at low substrate concentrations, BOD assays were conducted using NG and EA, singly and in combination.…”
Section: Bench-scale Ng Resultsmentioning
confidence: 99%
“…This finding is in agreement with previous work that reported a 3.1% decrease in NG concentration in shake-flask experiments in the absence of growth substrates. 21 To further investigate the issue of NG as a sole carbon source at low substrate concentrations, BOD assays were conducted using NG and EA, singly and in combination.…”
Section: Bench-scale Ng Resultsmentioning
confidence: 99%
“…Biotransformation of GTN was reported as taking place stepwise via the dinitrate and mononitrate isomers, with each successive step proceeding at lower rates (Accashian et al, 1998;Blehert et al, 1997;Christodoulatos et al, 1997;Meng et al, 1995;and Wendt et al, 1978). The accumulation and subsequent removal of GDNs occurred in the absence of detectable GMNs, indicating that GMN denitration was faster than GDN denitration (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated a stepwise GTN biotransformation pathway via the dinitrate and mononitrate glycerol ester, with successive steps proceeding at slower rates. Nitrate esters were undetectable in effluent samples from the continuous bioreactor, but pure cultures isolated from the continuous bioreactor and subsequently grown in batch bioreactors were incapable of complete GTN denitration (Wendt et al, 1978). The authors observed little or no reduction in GTN concentration in controls without supplemental carbon, suggesting that biological transformation (biotransformation) of GTN was a co-metabolic process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ducrocq et al (3,4) showed that certain yeast and mycelial fungi can convert GTN to a mixture of glyceryl dinitrates (GDNs) and glyceryl mononitrates (GMNs). Wendt et al (19), in their pioneering studies, proposed that the bacterial metabolism of GTN occurs via sequential denitration to GDN and GMN and speculated that the GMN was further denitrated to form glycerol. However, the degradation was not complete, as GDN and GMN were still present in the spent medium (19).…”
mentioning
confidence: 99%